1974
DOI: 10.1136/pgmj.50.586.513
|View full text |Cite
|
Sign up to set email alerts
|

Fatal outcome from administration of a salt emetic

Abstract: SummaryA case is described of the death of a young female patient following the administration of a salt emetic after a relatively minor overdose of a proprietary analgesic containing aspirin. It is suggested that death occurred as a direct consequence of the salt ingestion and that the dangers of this method of inducing emesis should be more widely appreciated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Four patients ingested excessive salt as part of a suicide attempt [15–18]. Seven patients (including our patient) were diagnosed of suffering of other psychiatric disorders [19–24]. Only one patient was a male, whilst all others were females.…”
Section: Discussionmentioning
confidence: 99%
“…Four patients ingested excessive salt as part of a suicide attempt [15–18]. Seven patients (including our patient) were diagnosed of suffering of other psychiatric disorders [19–24]. Only one patient was a male, whilst all others were females.…”
Section: Discussionmentioning
confidence: 99%
“…The patient and their relatives panic after taking the agent or when they are bitten by a snake; hence, they try some traditional techniques to remove the toxin from the body. [1516] In our study, we found that people still used age-old method of putting finger in the mouth to stimulate pharynx or using saline water in order to induce vomiting. The practice of applying tourniquet is still prevalent in cases of snakebite.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, 27 manuscripts reporting fatality from ingesting dietary salt were obtained. There were 35 fatalities reported, 19 in adults [ 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and 16 in children [ 6 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The fatalities were categorized by age ( Table 2 and Table 3 ).…”
Section: Resultsmentioning
confidence: 99%